Hak Asasi Manusia Dalam Perspektif Hukum Islam dan Undang-Undang Di Indonesia - Siti Azhara; Ulya Hafdhah Fajrillah; Lailan Husna; Shintia Sari Daulay (Tabayyun : Journal Of Islamic Studies, 2025)
Human Rights (HAM) are universal principles which emphasize that human dignity is a basic right that cannot be abolished. In Islamic law, Human Rights (HAM) are based on maqashid sharia, namely the main goal of sharia which functions to protect basic rights such as the right to life, religious freedom and justice. This view emphasizes that these rights are human nature and must be protected without discrimination. On the other hand, Law no. 39 of 1999 concerning Human Rights and the 1945 Constitution provide a positive legal structure that protects the human rights of every person in Indonesia. These two legal systems are in harmony in the basic principles of respect for human rights, although there are differences in the methods and implementation. Collaboration between Islamic law and Indonesian positive law is a challenge and opportunity to build a stronger legal basis for universal and contextually appropriate human rights protection for Indonesian society.